Anisotropic Fermi Surface and Quantum Limit Transport in High Mobility Three-Dimensional Dirac Semimetal Cd_{3}As_{2} - Yanfei Zhao; Haiwen Liu; Chenglong Zhang; Huichao Wang; Junfeng Wang; Ziquan Lin; Ying Xing; Hong Lu; Jun Liu; Yong Wang; Scott M. Brombosz; Zhili Xiao; et al. (Physical Review X, 2015)
Three-dimensional topological Dirac semimetals have a linear dispersion in 3D momentum space and are viewed as the 3D analogues of graphene. Here, we report angle-dependent magnetotransport on the newly revealed Cd_{3}As_{2} single crystals and clearly show how the Fermi surface evolves with crystallographic orientations. Remarkably, when the magnetic field lies in the [112] or [441[over ¯]] axis, magnetoresistance oscillations with only single period are present. However, the oscillation shows double periods when the field is applied along the [11[over ¯]0] direction. Moreover, aligning the magnetic field at certain directions also gives rise to double period oscillations. We attribute the observed anomalous oscillation behavior to the sophisticated geometry of Fermi surface and illustrate a complete 3D Fermi surface with two nested anisotropic ellipsoids around the Dirac points. Additionally, a submillimeter mean-free path at 6 K is found in Cd_{3}As_{2} crystals, indicating ballistic transport in this material. By measuring the magnetoresistance up to 60 T, we reach the quantum limit (n=1 Landau level) at about 43 T. These results improve the knowledge of the Dirac semimetal material Cd_{3}As_{2} and also pave the way for proposing new electronic applications based on 3D Dirac materials.